2006
DOI: 10.1021/jo052443x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Microwave Access to Polysubstituted Amidines from Imidoylbenzotriazoles

Abstract: Microwave reactions of primary and secondary amines with imidoylbenzotriazoles 6a-w gave diversely substituted amidines 7a-Aa in 76-94% yields. Convenient preparations of a variety of amides 5a-Ab (87-96%) and imidoylbenzotriazoles 6a-w (56-95%) have also been developed using microwave irradiation under mild conditions and short reaction times. These results demonstrate further the advantages of microwave synthesis and introduce a new application of imidoylbenzotriazoles in the preparation of polysubstituted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(46 citation statements)
references
References 55 publications
3
43
0
Order By: Relevance
“…26,27 Design of effective methodology for amide preparation stands as an excellent idea because of their significance in basic sciences, leading to many varieties of commercial and medicinal utilization and as crucial synthons in organic synthetic chemistry. 26,28 Therefore, it was envisaged that inserting of amide group into the sulfonamide moieties might lead to boosting or enhancement of antibacterial activity of such templates. Hence, it is conceivable to design the synthetic route in this present work in such a way to have amide functionality being incorporated within the framework of the synthesized sulfonamides.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Design of effective methodology for amide preparation stands as an excellent idea because of their significance in basic sciences, leading to many varieties of commercial and medicinal utilization and as crucial synthons in organic synthetic chemistry. 26,28 Therefore, it was envisaged that inserting of amide group into the sulfonamide moieties might lead to boosting or enhancement of antibacterial activity of such templates. Hence, it is conceivable to design the synthetic route in this present work in such a way to have amide functionality being incorporated within the framework of the synthesized sulfonamides.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of amidines by electrophilic activation of aliphatic secondary or tertiary amides using triflic anhydride was reported by Charette et al,27 but this approach is found to be less effective in the case of both aliphatic and aromatic primary carboxamides. Subsequent to this report related to the synthesis of amidines from secondary carboxamides, many research groups including Katritzky et al,28 Thakur et al,29 Loughlin et al,30a Shibasaki et al,30b and Bihel et al,30c contributed significantly in this area. Whereas these methodologies are suitable for secondary carboxamides, they are strictly not applicable for primary carboxamides.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In the last decade, some of the first examples yielded interesting results, which led to much research in this novel technique. [9][10][11][12][13][14][15][16][17][18][19] Dandia et al 20 reported a one-pot synthesis of novel spiro[pyrazolo [4,3-c] [1,5]benzothiazepines] with a 71% yield within 6-8 min using microwave irradiation. They also reported the synthesis of novel spiro[indole-pyrido [2,3-d]pyrimidines] by the reaction of in situ generated spiro[indole-dihydropyridine] and urea/CS 2 using basic alumina as a solid support or a few drops of DMF as a homogenizer under microwave irradiation for 3-4 min in 85-89% yield.…”
Section: Introductionmentioning
confidence: 99%